Tracer Study Analysis of Graduates of SMK Karsa Mulya Palangkaraya for Talent Mapping Adaptive to the Needs of Business and Industry - Rasmi Widya Rani; Veitzhal Rivai; Azis Hakim (Jurnal Ilmu Multidisiplin, 2025)
The purpose of the study was to analyze the results of the tracer study of graduates of SMK Karsa Mulya Palangkaraya, which became the basis for mapping talents associated with the needs of business and industry. The existence of a match between the competencies of graduates of SMK Karsa Mulya Palangkaraya and the demands of business and industry (Dudi) is one of the indicators of success in vocational education. This study used a Mixed Methods approach with a Sequential Explanatory design, which is a quantitative approach followed by qualitative to provide an in-depth understanding of the preliminary results. This approach was chosen because the purpose of the study was not only to measure the level of absorption of SMK Karsa Mulya Palangkaraya graduates in the world of work, but also to map the potential and talents of graduates based on the needs of the business and industrial world (DUDI). The data collected included graduate employment, curriculum relevance, skills used in the workplace, and waiting time in getting a first job. The results show that most graduates work according to their expertise but there are still gaps in some technical and non-technical skills needed in the industrial world. The study recommends increased collaboration between SMK Karsa Mulya Palangkaraya and industry partners, as well as continuous evaluation of the curriculum and apprenticeship program.